FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING PADA KANTOR PELAYANAN PAJAK PRATAMA PALEMBANG ILIR TIMUR - Rahayu, Pipit Fitri (MOTIVASI, 2017)
Purpose - The purpose of this research was the factors that influance behavior individual taxpayer in using e-filing. Design/methodology - This research used primary data obtained from questionnaires. The sample used were the individual taxpayer in the Tax Office Pratama Palembang Ilir Timur that using e-filing. The amount sample of individual taxpayer in this research were 390, but the amount of questionnaires that can processed is 152. The sampling technique used was random sampling. The  data  analysis  technique  used was the Sturctural Equation Model (SEM) analysis test by using SmartPLS software version 3.0. Findings – The research showed that the complexity of e-filing has a significant positive to perceived usefulness of e-filing, complexity of e-filing has not significant to behavior individual taxpayer in using e-filing, ease of use e-filing has not significant to behavior individual taxpayer in using e-filing, ease of use e-filing has a significant positive to perceived usefulness of e-filing, ease of use e-filing has a significant behavior individual taxpayer in using e-filing, perceived usefulness of e-filing has a significant positive to behavior individual taxpayer in using e-filing.